CORRELATION OF WORK LOADS WITH WORK FATIGUE AT HEALTH WORKERS TEAM WHO CARRIED OUT A 24-HOUR SHIFT IN NGANTANG INPATIENT HEALTH CENTER - Surya, Oky Anggara; Amarin Yudhana; M. Ali Sodik (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2018)
The high public interest in health services without being balanced with the quantity and quality of adequate human resources triggers an increase in workload resulting in physical fatigue which can reduce performance of health workers. The purpose of this study was to determine the correlation of work loads with work fatigue at health workers team that implements a 24-hour shift in Ngantang Inpatient Health Center. Research design of this study was observational with cross sectional approach. Population studied was all health workers team who carried out 24-hour shift in Ngantang Inpatient Health Center amount 38 people, with Simple Random Sampling technique obtained sample 35 respondents. Independent variable was workload with dependent variable work fatigue. Data collection using a questionnaire. Data analysis with Spearman rho test at α = 0.05. The results showed almost half of respondents had workload in the high category, amount 16 respondents (45.7%) and most respondents had  work fatigue in very tired category, amount 21 respondents (60.0%). The analysis results showed that there was correlation of work loads with work fatigue at health workers team that implements a 24-hour shift in Ngantang Inpatient Health Center. (p-value = 0.009 <a = 0.05). The high workload of health workers without being balanced by adequate rest periods triggers an increase in fatigue. High levels of fatigue can increase the risk of performance degradation due to reduced physical ability and concentration.